THE MODERATING ROLE OF WORK DIVISION IN THE INFLUENCE OF PSYCHOLOGICAL CAPITAL AND PSYCHOLOGICAL WELL-BEING AMONG PERSONNEL IN THE AIRLINE BUSINESS SECTOR - Anekjumnongporn, Pongsavake (Journal of MCU Nakhondhat, 2026)
This research article aims to examine the moderating role of work division in the relationship between psychological capital and psychological well-being among personnel in the airline business sector. A quantitative research design was employed, and data were collected from 129 airline personnel selected through a multi-stage sampling technique. The research instruments consisted of a psychological capital questionnaire and a psychological well-being questionnaire, both of which were validated for content validity and reliability in accordance with established statistical criteria. Data analysis was conducted using statistical software for social sciences, applying descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics through multiple linear regression analysis to test causal relationships and moderating effects. The research findings revealed that 1) psychological capital exerts a significant positive influence on the psychological well-being among personnel in the airline business sector. Moreover, work division was found to function as a significant moderating variable in this relationship. Specifically, the interaction effects between psychological capital and work division roles significantly influenced psychological well-being among personnel working in air cargo and ramp operations, in-flight passenger services, and ground passenger services. These moderating effects were statistically significant at the .01 and .05 levels, respectively. The results underscore the critical role of occupational and departmental contexts in shaping the effectiveness of psychological capital in enhancing employee well-being. The study provides empirical evidence that supports the integration of psychological capital development into human resource management strategies tailored to specific operational units within the airline industry. Such an approach may contribute to the sustainable promotion of psychological well-being and organizational effectiveness in a highly demanding and competitive service environment.